Synthesis, characterization and photovoltaic behaviours of peripheral and non-peripheral tetra-[4-(4-octylpiperazin-1-yl)phenoxy] substituted zinc(II), cobalt(II), copper(II) and indium(III) phthalocyanines - (:unkn) unknown (ELSEVIER SCIENCE SA, 2019)
The synthesis of zinc(II), cobalt(II), copper(II) and indium(III)(OAc) phthalocyanines carrying four 4-(4-octylpiperazin-1-yl) phenoxy moieties in peripheral/non-peripheral positions were performed by the cyclotetramerization of compounds 4-[4-(4-octylpiperazin-1-yl) phenoxy] phthalonitrile or 3-[4-(4-octylpiperazin-1-yl) phenoxy] phthalonitrile with respective metal salts. The novel phthalonitriles and phthalocyanines were characterized by elemental and spectroscopic analysis, including H-1 NMR, C-13 NMR, FT-IR, UV-Vis spectral and MALDI-TOF mass data. To clarify the influence of the position of substituent group and the variety of the central metal atom on the photovoltaic performance, bulk heterojunction devices by using phthalocyanines with different blend ratio, as donor was fabricated and characterized.
Keywords: Phthalocyanine; BHJ; PC61BM; Conversion efficiency; OPEN-CIRCUIT VOLTAGE; SOLAR-CELLS; METAL-FREE; METALLOPHTHALOCYANINES; PERFORMANCE; SENSORS; FILMS